Spatial extent, timing, and causes of channel incision, Black Vermillion watershed, northeastern Kansas - Meade, Benjamin K. (Kansas State University, 2009)
The Black Vermillion River (watershed area = 1310 square kilometers) contributes runoff and sediment into Tuttle Creek Reservoir, a large federal reservoir (volume = 327 million cubic meters) northeast of Manhattan, Kansas. Tuttle Creek, completed in 1962, is filling with sediment faster than other federal reservoirs in the region. The Reservoir’s conservation pool is about 40 percent full of sediment and is predicted to fill by 2023. Debate rages over the relative contribution of sediment from upland sources (largely croplands and pasture) versus channel incision. In the Black Vermillion watershed, bedrock is overlain in most of the watershed by pre-Illinoian age easily erodible glacial till and loess. Row crop agriculture is the most common land use in the watershed and stream channels are incised and prone to frequent flooding and channel instability. This research focused on the spatial extent, timing, and causes of channel incision in the Black Vermillion watershed. I conducted a watershed-wide survey of channel cross-sections in 56 locations repeated at sites that had been surveyed 45 years ago by the Soil Conservation Service. Further, I collected channel cross sections in 2008 at a total of 51 more locations for a total of 107 study sites. Channel depths between 1963 and 2008 increased by a mean of 1.6 meters (maximum = 5.2 meters). Most channels throughout the watershed have incised, are actively incising, or incising and widening. Statistical testing between channel depths as measured in 1963 and 2008 showed that the amount of incision was related to land use/land cover, riparian buffer widths, upstream drainage area, and geology. As channels incise, they progress through six stages of channel evolution, which complicates the relationship between channelization and incision. Channel stage, as identified in the field, was statistically related to geology, occurrence and timing of channelization, land use/land cover, and upstream drainage area. Channelization has reduced channel length by a significant portion and was identified as one of the leading causes of incision. This finding suggests that planting buffers and/or expanding existing buffers along streams should be encouraged in the watershed to alleviate flooding and channel instability.
Keywords: channel incision; agricultural streams; Black Vermillion River; channel instability; channelization; Kansas rivers; Geography (0366); Geology (0372); Physical Geography (0368)